2021
DOI: 10.18476/insy.v03.a4
|View full text |Cite
|
Sign up to set email alerts
|

Type specimens of the South American terrestrial gastropods described by Henry Suter

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Here, it is also recorded from the Corrientes Province (Argentina). The record for Santa Fe Province (Miquel & Parent, 1996) was erroneous (Salvador, 2021); the image of the specimen does not resemble G. iheringi but to an indeterminate species of Gastrocopta. Mentions of G. iheringi from Peru (Ramírez et al, 2003) and Venezuela (Thompson & López, 1996) need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is also recorded from the Corrientes Province (Argentina). The record for Santa Fe Province (Miquel & Parent, 1996) was erroneous (Salvador, 2021); the image of the specimen does not resemble G. iheringi but to an indeterminate species of Gastrocopta. Mentions of G. iheringi from Peru (Ramírez et al, 2003) and Venezuela (Thompson & López, 1996) need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%